Análisis del sistema de protección de puesta a tierra y apantallamiento eléctrico en una planta minera. - Orbea García, Jefferson Marcelo (2023)
This research work deals with the analysis of the grounding and electrical shielding protection system in the Agroindustrial El Corazón mining flotation plant. The proposal arises from the need of the electrical department to identify disturbances and verify the correct performance of the grounding system (SPT) and the evaluation of the feasibility and design of a protection system against atmospheric discharges. The SPT is studied with measurements of the soil resistivity, the geometry and the resistance of the three meshes. In the ETAP software, a 2-layer soil model is established, the geometries of each mesh are loaded and the finite element technique is applied to obtain the resistance, touch and step voltage of each mesh. The simulation shows that mesh 1 generates a touch voltage of 1823V, exceeding the tolerable limit of 988V according to IEEE-80. Proposals for equipotentialization of the meshes are made and the graphs of the potential gradients are analyzed. With the adaptations, equipotentiality is obtained throughout the installation and a maximum step voltage of 900V and a uniform potential distribution are obtained. Regarding the design of the protection system against atmospheric discharges, the risk level of NPR=1 was determined. For external protection, the electrogeometric method of rolling spheres is used by placing lightning capture spikes in ten locations in the plant, downspouts and goose-foot type ground outlets are determined to drain lightning currents. Regarding internal protection, the study is carried out on the SPDs for medium voltage on the MV side and the SPDs type 1 and 2 combined, Type 2 and Type 3 that are installed in certain low voltage areas.